Probiotic attributes and safety profile of AKM Lab-01: a novel Akkermansia muciniphila strain combating obesity and metabolic disorders in diet-induced obese mice - Huang, Baojia; Xian, Yibo; Xue, Wenbin; Pu, Zilun; Kong, Ping; Li, Peifen; Zhao, Yingying; Tai, Lihong; Chen, Zhipeng; Lan, Zhou; Liu, Hong-Wei; Jiang, Xianzhi; et al. (Frontiers in Microbiology, 2026)
Obesity is a global health crisis associated with numerous chronic diseases. Recent studies highlight the role of gut microbiota, particularly Akkermansia muciniphila (A. muciniphila), in regulating metabolism and improving obesity-related disorders. In this study, we isolated 222 strains of Akkermansia from healthy human feces. Using a genomic dataset of 26 selected strains (from our isolation) plus 97 from NCBI, phylogenetic analysis revealed that there are eight Akkermansia species including two major clades: A. muciniphila and Akkermansia massiliensis, along with two potential novel candidate species. One strain, designated AKM Lab-01, demonstrated significant efficacy in reducing weight gain in a high-fat diet (HFD)-induced obese mouse model, with a 10% weight reduction observed after 4 weeks. Metabolic parameters (e.g., blood glucose, lipids, and insulin resistance) and liver/kidney function were also improved. AKM Lab-01 exhibited strong probiotic properties, including pH and bile salt tolerance, high auto aggregation capacity, and antibiotic sensitivity. Further investigations revealed that both live and processed forms (pasteurized and powdered) of AKM Lab-01 effectively mitigated obesity and associated metabolic disorders in diet-induce obese mice. A 90-day dietary exposure study in mice demonstrated no adverse effects at doses up to 8 × 1010 total florescent unit (TFU) a day. In accordance with EFSA guidelines and applying an uncertainty factor of 200, a daily intake of 1 × 1012 TFU is deemed safe for human consumption. Collectively, these findings highlight the potential of AKM Lab-01 as a promising probiotic for the prevention and treatment of obesity and related metabolic diseases.